Transformation-based Optimizations Framework (ToF) for Workflows and its Security issues in the Cloud Computing (International Journal of Engineering and Computer Science, 2015)
A general transformation-based optimization framework for workflows in the cloud. Specifically, ToF formulates six basic workflow transformation  operations.  An  arbitrary performance and  cost optimization  process can be represented as a transformation plan (i.e., a sequence of basic transformation operations). All transformations form a huge optimization space. We further develop a cost model guided planner to efficiently find  the  optimized  transformation for  a predefined goal and our experimental results demonstrate the effectiveness of ToF in optimizing the performance and cost in comparison with other existing approaches. cloud computing offers its customers an economical and convenient pay-as-you- go service model, known also as usage-based pricing. Cloud customers pay only for the actual use of computing resources, storage, and band-width, according  to  their  changing  needs,  utilizing  the cloud’s  scalable  and  elastic  computational capabilities.  In  particular,  data transfer costs  (i.e., bandwidth) is an important issue when trying to minimize costs